Is there any future of optical discs? - Kryuchyn, A.A.; Petrov, V.V.; Kostyukevych, S.O.; Kostyukevych, K.V.; Kudryavtsev, A.A.; Moskalenko, N.L. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
Considered in this paper are causes for cutting compact discs out of information technology market. It has been shown a search of new technological solutions for efficient use of CDs in archive data storage.